1995
DOI: 10.2527/1995.73102931x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding wet corn gluten feed to reduce subacute acidosis in cattle.

Abstract: Two experiments were conducted to evaluate the effects of feeding wet corn gluten feed (WCGF) on subacute acidosis in cattle. In Exp. 1, 60 individually fed yearling steers (270 +/- 22 kg BW) were used in a 5 x 2 factorial arrangement of treatments. Steers were assigned to one of five dietary treatments: 1) dry-rolled corn (DRC), 2) 35% WCGF fed d 1 to 132, 3) 86.5% WCGF fed d 1 reduced to 35% WCGF by d 19 and increasing the proportion of DRC, 4) 86.5% WCGF fed d 1 to 132, or 5) 94.5% WCGF fed d 1 to 132. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
2
7

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 14 publications
(18 reference statements)
1
48
2
7
Order By: Relevance
“…Additionally, daily gain was not affected ( P > .15) by protein supplement. Similarly, Krehbiel et al (1995) observed no response to supplemental escape protein in yearling steers fed diets including up to 94.5% WCGF. However, Trenkle (1993) observed improved gains in yearling cattle fed approximately equal portions of DRC and dry corn gluten feed when the diet was supplemented with a combination of urea and soybean meal, compared with urea alone.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, daily gain was not affected ( P > .15) by protein supplement. Similarly, Krehbiel et al (1995) observed no response to supplemental escape protein in yearling steers fed diets including up to 94.5% WCGF. However, Trenkle (1993) observed improved gains in yearling cattle fed approximately equal portions of DRC and dry corn gluten feed when the diet was supplemented with a combination of urea and soybean meal, compared with urea alone.…”
Section: Resultsmentioning
confidence: 97%
“…In a finishing trial, Krehbiel et al (1995) fed varying levels of WCGF to yearling Hereford steers with or without addition of escape protein. The addition of escape protein did not result in an increase in performance.…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, high levels (i.e., >50% diet DM) of WCGF reduce dietary energy to an extent that overrides the beneficial effects of highly digestible fiber addition to finishing diets. Krehbiel et al (1995) and Sindt et al (2002) observed a reduction in ruminal VFA concentration and an increase in ruminal pH as WCGF replaced corn grain, indicative of reduced acidosis insult with WCGF inclu-sion. Few studies have evaluated reducing roughage levels in finishing diets containing WCGF.…”
Section: Feedlot Performancementioning
confidence: 99%
“…This response is thought to occur as a result of WCGF decreasing rumen starch load and the incidence of ruminal acidosis (Krehbiel et al, 1995). Typically, roughages such as alfalfa hay (AH) are used to control acidosis in finishing diets, and an increase in DMI and ADG is often observed with a small amount (i.e., ≤10% diet DM) of roughage inclusion (Stock et al, 1990;Huffman et al, 1992;Shain et al, 1999).…”
mentioning
confidence: 99%